2020
DOI: 10.1093/ee/nvaa008
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Influence of Ambient Temperature on the Interactions Between the Stable Fly (Diptera: Muscidae) and Its Natural Enemy Spalangia cameroni (Hymenoptera: Pteromalidae) to Assess Consequences of Climate Change

Abstract: A simulation model was used to predict how temperature influences biological control of stable flies (Stomoxys calcitrans (L.)) by the pupal parasitoid Spalangia cameroni. Temperature, which was either constant or fluctuated due to seasonal variation and/or environmental stochasticity, was modeled as a first order autocorrelation process. The simulations showed that stable flies could tolerate a wider temperature interval than expected from their thermal performance curve (TPC). This was attributed to the fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Biological parasites were released on the farm as part of protocols for controlling immature stages, aiming to establish sustainable reductions in fly populations [5][6][7]. Previous studies have indicated that S. cameroni and M. raptor successfully reproduced on both fly species, S. calcitrans and Musca domestica, in dairy farming [22][23][24]. Azevedo et al [20] have already evaluated the predation capacity of the predatory mites from the Macrochelidae family on fly eggs and neonates.…”
Section: Parasitoids and Predator Agents Releasementioning
confidence: 99%
“…Biological parasites were released on the farm as part of protocols for controlling immature stages, aiming to establish sustainable reductions in fly populations [5][6][7]. Previous studies have indicated that S. cameroni and M. raptor successfully reproduced on both fly species, S. calcitrans and Musca domestica, in dairy farming [22][23][24]. Azevedo et al [20] have already evaluated the predation capacity of the predatory mites from the Macrochelidae family on fly eggs and neonates.…”
Section: Parasitoids and Predator Agents Releasementioning
confidence: 99%